RELATIONSHIP MARKETING PADA UPSCALE RETAILING : Hubungan Antara Kepuasan Konsumen Dengan Loyalitas Pada Pramuniaga Serta Toko dan Word of Mouth - Harsini Soetomo (Universitas Trisakti, 2004)
Rapidly changing competitive environments are forcing fims to build iong-tem relationships with their partner. In upscale retailing consumers need to be served personall, because the products sold by the retailer are expensive. The customers must convince the product is appropriate for herhim. The role of retail salesperson is veryimportantto help the consumers in deciding the prodưct The salesperson could build long-termrelationships with the customer by giving customer satisfaction. The benefit of Relationship marketing between salesperson and the customers in upscale retailing setting for the store is i.e. customers toyalty and the customers will build positive word of mouth This study examined the relationship between customers satisfaction (to the store and salesperson) and customers loyalty (to the store and salesperson) and word of mouth in upscale retailing setting. Questioner administered to 193 customers' upscale retailer in Jakarta. Using Structural Equation Modeling support by AMOS 4.1. This study supported all the proposed hypotheses.